Law nº 13.415 and its contributions in the context of youth citizenship education in high school (Research, Society and Development, 2021)
This article aims to analyze the Law No. 13.415, of February 2017 and its contributions in the context of youth citizenship education in high school. For this, we carried out a bibliographic and documentary research, based on a set of references, laws, and decrees. Therefore, we could have a deeper analysis, in order to understand the processes that led to the construction of the current high school counter-reform in the country, linked to the categories Work and Education; as well as the challenges that arise for the strengthening of educational policies for Brazilian youth.